Self‐management strategies used by head and neck cancer survivors following completion of primary treatment: A directed content analysis. Issue 12 (26th May 2017) - Dunne, Simon; Mooney, Orla; Coffey, Laura; Sharp, Linda; Timmons, Aileen; Desmond, Deirdre; Gooberman‐Hill, Rachael; O'Sullivan, Eleanor; Keogh, Ivan; Timon, Conrad; Gallagher, Pamela
Abstract: Objective: Head and neck cancer (HNC) survivors encounter unique challenges following treatment. This study aimed to identify self‐management strategies that HNC survivors use to overcome these posttreatment challenges. Methods: Twenty‐seven individuals from 4 designated cancer centres in Ireland were interviewed about self‐management strategies that helped them overcome challenges following HNC treatment. Interviews were audio‐recorded, transcribed, and analysed using directed content analysis. Results: Twenty self‐management strategy types (encompassing 77 specific strategies) were identified. The most frequently used self‐management strategy types were self‐sustaining (used by 26 survivors), self‐motivating (n = 25), and proactive problem solving (n = 25). The most frequently used specific strategies were adaptive approaches to ongoing physical consequences of HNC and its treatment (n = 24), customising dietary practices (n = 24), and maintaining a positive outlook (n = 22). Conclusions: The study identified strategies that helped HNC survivors to self‐manage posttreatment challenges. This information could inform the design/development of self‐management interventions tailored towards HNC survivors.